Seroprevalence and Associated Risk Factors of Bovine Viral Diarrhea in the Dairy Cattle of Rupandehi District of Nepal - Tandan, P.; Paudel, Madhav (International Journal of Applied Sciences and Biotechnology, 2023)
Bovine Viral Diarrhea (BVD) is a contagious disease caused by Bovine Viral Diarrhea Virus (BVDV), which significantly impacts cattle health and productivity, leading to substantial economic losses for farmers. The Rupandehi district in Nepal, which shares an open border with India, is particularly vulnerable to the introduction and spread of BVD. Consequently, the objective of this research was to examine the prevalence of Bovine Viral Diarrhea Virus (BVDV) infections and the associated risk factors that contribute to it in the Rupandehi district of Nepal. A two-phase random sampling method was used, where a total of 92 blood samples were obtained from female cattle from Devdaha, Sainamaina, Tilottama, and Suddhodhan Municipality. Serological testing using ID-Screen® BVD p80 Antibody Competition ELISA revealed that 10 samples (10.86%) tested positive for BVDV infection. Cattle aged over 5 years exhibited a higher seroprevalence rate in comparison to other age groups of 3-5 years and < 3 years. Notably, Holstein (26.7%) and Holstein cross (15.4%) cattle exhibited a significantly higher prevalence compared to jersey, jersey cross, and indigenous cattle (p<0.05). None of the assessed risk factors, including repeat breeding (infertility), history of abortion, history of retained placenta, diarrhea, and neonatal death, were found to be statistically significant in relation to the seroprevalence. The findings of this study indicate a comparatively higher seroprevalence rate than previous studies conducted in Nepal. Furthermore, the farmers of the affected herds displayed a lack of awareness regarding BVD and its presence on their farms. These results emphasize the urgent need for the relevant authorities to recognize BVD as a serious issue and take necessary nationwide measures for its control and eradication. Int. J. Appl. Sci. Biotechnol. Vol 11(3): 128-134